Transitions between informal and formal employment: results from a worker survey in Bangladesh - Gutierrez, Italo A.; Kumar, Krishna B.; Mahmud, Minhaj; Munshi, Farzana; Nataraj, Shanthi (© 2019 Springer Berlin Heidelberg, 2019)
This article was published in IZA Journal of Development and Migration [© 2019 Springer Berlin Heidelberg] and the definite version is available at: https://doi.org/10.1186/s40176-019-0141-2 The Journal's website is at: https://link.springer.com/article/10.1186/s40176-019-0141-2